Pengaruh Kepemimpinan Transaksional, Sistem Reward, dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Rumah Sakit Umum Daerah Kabupaten Wakatobi - Ahmad Daulani; La Ode Muhammad Syafaruddin; Puter Rasid (CV. Creative Tugu Pena, 2024)
The objectives to be achieved in this research are: 1) Analyze the influence of transactional leadership on performance; 2) Analyze the influence of the reward system on employee performance; 3) Analyze the influence of the work environment on employee performance; 4) Analyze the influence of transactional leadership, reward systems and work environment on employee performance. The sample taken was determined to be 63 people. Collecting data in this research is taking samples using a questionnaire by distributing questionnaires to respondents. Based on the results of research analysis and discussion on the influence of transactional leadership style, reward systems and work environment on the performance of District Regional Hospital employees. Wakatobi, the following conclusions were obtained: 1) Transactional leadership has no significant effect on employee performance. The application of leadership that focuses attention on interpersonal transactions between leaders and subordinates which involves the relationship between the two can improve the performance of District Hospital employees. Wakatobi; 2) The reward system has a positive and significant effect on employee performance. This fact shows that the rewards received by employees, both in financial and non-financial forms, are able togood rewards consisting of bonuses/incentives, overtime pay and social assistance are able to improve the performance of District Hospital employees. Wakatobi; 4) The work environment has a positive and significant effect on employee performance. This fact shows that a good work environment can improve the performance of District Hospital employees Wakatobi